Survey on privacy preserving techniques for blockchain - Zonghui WANG; Shengli ZHANG; Shi JIN; Hui WANG (物联网学报)
Blockchain is a kind of distributed ledger technology with the characteristics of decentralization,security reliability,tamper-proof and programmable.The open and transparent feature of the blockchain system has seriously threatened the transaction privacy of users,and the corresponding privacy problem solution is designed for different application scenarios.Firstly,the basic working principle of block chain technology was introduced,and typical privacy issues was introduced in blockchain,such as transaction privacy and account privacy.Secondly,the existing typical blockchain privacy protection schemes were divided into three types:mixed-coin technology,cryptography technology and secure channel technology,and presents a comprehensive and comprehensive introduction to this three privacy protection schemes; Finally,the blockchain data privacy protection technology was analyzed,the application and development on IoT security were prospeted.